1983
DOI: 10.1111/j.1365-2133.1983.tb04583.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic observations on dapsone in dermatitis herpetiformis

Abstract: The pharmacokinetics of dapsone (DDS) and monoacetyldapsone (MADDS) following an oral dose of 150 mg DDS were studied in sixteen patients with dermatitis herpetiformis and seven normal subjects. No differences in DDS disposition were observed between the two groups. The maintenance dose of DDS for individual patients was not significantly correlated with jejunal biopsy morphology, DDS or MADDS half-lives, or the area under the plasma concentration-time curves for DDS or MADDS. DDS plasma protein binding was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…ment of acetylator phenotype (Adam et al, 1984;Horai et al, 1985;Hutchings et al, 1984). Swain et al (1983) noted that after a single dose of 150 mg no patients or volunteers suffered adverse effects. However, methaemoglobin levels were not determined in these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ment of acetylator phenotype (Adam et al, 1984;Horai et al, 1985;Hutchings et al, 1984). Swain et al (1983) noted that after a single dose of 150 mg no patients or volunteers suffered adverse effects. However, methaemoglobin levels were not determined in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Dapsone is also used as a malarial prophylatic with pyrimethamine (Bruce-Chwatt, 1982). It is effective in the treatment of dermatitis herpetiformis (Swain et al, 1983), Pneumocystis carinii in AIDS patients (Green et al, 1988) and has been used in rheumatoid arthritis (Grindulus & MacConkey, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…It has a relatively long elimination half-life (Ahmad & Rogers, 1980a;Gelber et al, 1971;Lammintausta et al, 1979;Peters et al, 1981;Swain et al, 1983). Enterohepatic circulation occurs (Neuvonen et al, 1980) and the drug is extensively bound to serum proteins (Ahmad & Rogers, 1980a).…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Ellard et al (1974) showed that control of symptoms of patients with dermatitis herpetiformis was not correlated significantly to plasma DDS or MADDS concentrations but adverse effects (methaemoglobinaemia and Heinz-body formation) were correlated significantly to plasma DDS. Swain et al (1983) studied the pharmacokinetics of DDS in patients with dermatitis herpetiformis who needed doses of DDS ranging from 50 mg/week to 700 mg/day to control the rash. Plasma DDS and MADDS were monitored after a single 150 mg oral dose of DDS.…”
Section: Introductionmentioning
confidence: 99%